Interface engineering toward enhanced efficiency of planar perovskite solar cells. Issue 1 (1st December 2015) - Jiang, Lu-Lu; Cong, Shan; Lou, Yan-Hui; Yi, Qing-Hua; Zhu, Jun-Tong; Ma, Heng; Zou, Gui-Fu
Abstract : Perovskite solar cell performance was improved significantly by introducing 4, 7-Diphenyl-1, 10-phenanthroline (Bphen) doped with bis(2-methyldibenzo-[ f, h ]quinoxaline) (Ir(MDQ)2 (acac)) to modify the interface between perovskite (CH3 NH3 PbI3− x Cl x )/PCBM (phenyl-C61-butyric acid methyl ester) and an Ag electrode. Abstract : Interface engineering is an efficient method for improving the performance of planar perovskite solar cells (PSCs). In this paper, the performance of PSCs was improved significantly by introducing 4, 7-diphenyl-1, 10-phenanthroline (Bphen) doped with bis(2-methyldibenzo-[ f, h ]quinoxaline) (Ir(MDQ)2 (acac)) to modify the interface between perovskite (CH3 NH3 PbI3− x Cl x )/PCBM (phenyl-C61-butyric acid methyl ester) and an Ag electrode. The power conversion efficiency (PCE) was enhanced up to 15.87%, compared with 10.77% for the reference device without interlayer modification. It was found that the enhanced PCE was attributed to the better interface contact between the perovskite and Ag cathode. A suitable interface roughness is beneficial for reducing the leakage current and the probability of carrier recombination, resulting in an enhanced fill factor and thus improved device efficiency.